Prognostic Value of Clinical Tests in Neonates With Hypoxic-Ischemic Encephalopathy Treated With Therapeutic Hypothermia: A Systematic Review and Meta-Analysis - Liu, Weiqin; Yang, Qifen; Wei, Hong; Dong, Wenhui; Fan, Ying; Hua, Ziyu (Frontiers in neurology, 2020)
There remains an unmet clinical need for markers that predict outcomes in the hypothermia-treated (HT) infants with HIE. The aim of this meta-analysis was to investigate the prognostic accuracy of currently available clinical tests performed in the immediate post-natal period for predicting neurological outcomes between 18 months and 3 years of age in HT near-term and term infants with perinatal asphyxia and HIE. A comprehensive review of the Embase, Cochrane library, and PubMed databases was performed to identify studies that evaluated the prognostic value of clinical tests for neurological outcomes in HT near-term and term infants with perinatal asphyxia and hypoxic-ischemic encephalopathy. Pooled sensitivity and specificity with corresponding 95% confidence intervals and area under the receiver operating characteristic (ROC) curve (AUC) were calculated. Of the 1,144 relevant studies, 26 studies describing four clinical tests conducted in 1458 HT near-term or term infants were included. For predicting an unfavorable neurological outcome, of the imaging techniques, MRI within 2 weeks of birth performed best on sensitivity 0.85 (95% 0.79-0.89), specificity 0.72 (95% 0.66-0.77), and AUC 0.88; among the neurophysiological tests, multichannel EEG (Electroencephalogram) demonstrated the sensitivity 0.63 (95% 0.49-0.76), specificity 0.82 (95% 0.70-0.91), and AUC 0.88, and for aEEG (amplitude-integrated electroencephalography) background pattern pooled sensitivity, specificity and AUC were 0.90 (95% 0.86-0.94), 0.46 (95% 0.42-0.51), and 0.78 whereas for SEPs (Somatosensory evoked potentials), pooled sensitivity and specificity were 0.52 (95% 0.34-0.69), 0.76 (95% 0.63-0.87), and AUC 0.84, respectively. In the wake of the era of TH, MRI and neurophysiological tests (aEEG or EEG) were promising predictors of adverse outcomes, while SEPs need high-quality studies to confirm the findings. Continued follow-up of the children and well-designed large prospective studies are essential to determine whether these benefits are maintained in later childhood.